A novel air-conditioning system for proactive power demand response to smart grid. (15th September 2015) - Yan, Chengchu; Xue, Xue; Wang, Shengwei; Cui, Borui
Highlights: A novel air-conditioning system with proactive demand response is proposed. The system can significantly reduce the storage volume of the chilled water tank. Demand side bidding and demand as frequency controlled reserve can be implemented. No impact on occupants when demand response is used in the proposed system. Abstract: Power demand response is considered as one of the most promising solutions in relieving the power imbalance of an electrical grid that results a series of critical problems to the gird and end-users. In order to effectively make use of the demand response potentials of buildings, this paper presents a novel air-conditioning system with proactive demand control for daily load shifting and real time power balance in the developing smart grid. This system consists of a chilled water storage system (CWS) and a temperature and humidity independent control (THIC) air-conditioning system, which can significantly reduce the storage volume of the chilled water tank and effectively enable a building with more flexibility in changing its electricity usage patterns. The power demand of the proposed air-conditioning system can be flexibly controlled as desired by implementing two types of demand response strategies: demand side bidding (DSB) strategy and demand as frequency controlled reserve (DFR) strategy, in respond to the day-ahead and hour-ahead power change requirements of the grid, respectively. Considerable benefits (e.g., energy and cost savings) can be achieved for both the electricity utilities and building owners under incentive pricing or tariffs. A case study is conducted in a simulation platform to demonstrate the application of the proposed system in an office building.